Sensitivity Analysis of Geometric Parameter of the Stress in Bottom of Flexspline of Very Short Cup-shaped and Hat-shaped Harmonic Gear - Xing Jingzhong; Zhang Ze; Chen Xiaoxia; Yao Yunpeng (Jixie chuandong)
The stress in bottom of flexspline will increase rapidly with ratio of length to diameter of the harmonic gear. In order to decrease the stress in bottom of very short cup flexspline,the solid finite element models of parametric cup-shaped and hat-shaped flexspline are established,and the maximum stress and its distribution rule under the assembly state and load condition are calculated respectively. The effects of the geometric parameters such as the ratio of length to diameter,width of the diaphragm and fillet radius on the maximum assembly stress and load stress in the bottom of the flexspline are compared and calculated. The study shows that the very short cup-shaped flexspline is capable of small loading transmission,while the hat-shaped flexspline is suitable for large loading transmission. And much lower stress will be produced in hat-shaped flexspline by increasing width of diaphragm.